1999
DOI: 10.1037/0278-7393.25.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Representational momentum for rotations in depth: Effects of shading and axis.

Abstract: Representational momentum is a positive memory distortion for an object's final position following the presentation of an implied event (J.J. Freyd, 1987). Positive memory distortions occur when observers accept test positions beyond the final presented position, or forward along the implied trajectory, as the same more readily than positions behind the final position. Four experiments explored implied events depicting rotations about various depth axes in shaded and silhouette conditions. Positive memory dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
(147 reference statements)
5
37
1
Order By: Relevance
“…Weighted means Consistent with previous studies of displacement in memory for the spatial location of a target (e.g., Hayes & Freyd, 2002;Hubbard et al, 2009;Munger, Solberg, Horrocks, & Preston, 1999), estimates of the direction and magnitude of displacement were determined by calculating a weighted mean (the sum of the products of the proportion of same responses and the distance of the probe from the initial location of the target, in pixels, divided by the sum of the proportions of same responses) for each participant for each condition. The sign of a weighted mean indicated the direction of displacement (i.e., a minus sign indicated displacement in the direction opposite to target motion; a plus sign indicated displacement in the direction of target motion), and the absolute value of a weighted mean indicated the magnitude of displacement (i.e., a larger absolute value indicated a larger magnitude of displacement).…”
Section: Resultsmentioning
confidence: 99%
“…Weighted means Consistent with previous studies of displacement in memory for the spatial location of a target (e.g., Hayes & Freyd, 2002;Hubbard et al, 2009;Munger, Solberg, Horrocks, & Preston, 1999), estimates of the direction and magnitude of displacement were determined by calculating a weighted mean (the sum of the products of the proportion of same responses and the distance of the probe from the initial location of the target, in pixels, divided by the sum of the proportions of same responses) for each participant for each condition. The sign of a weighted mean indicated the direction of displacement (i.e., a minus sign indicated displacement in the direction opposite to target motion; a plus sign indicated displacement in the direction of target motion), and the absolute value of a weighted mean indicated the magnitude of displacement (i.e., a larger absolute value indicated a larger magnitude of displacement).…”
Section: Resultsmentioning
confidence: 99%
“…Kerzel (2002c) pointed out that in many previous studies, direction of rotation was blocked, and he reported that forward displacement was greatly diminished if direction of rotation varied within blocks (i.e., varied from trial to trial). However, robust forward displacement has been reported when the direction of rotation Munger, Solberg, Horrocks, & Preston, 1999) or translation (Hubbard, 1990;Hubbard & Bharucha, 1988) varied randomly within observers and across trials within a single block, and so forward displacement does not depend solely on across-trial expectancies of motion in a specific direction. A consistently larger forward displacement for either clockwise or counterclockwise rotation is usually not reported (e.g., Freyd & Johnson, 1987;Kelly & Freyd, 1987), but as was noted earlier, targets that rotate downward typically exhibit larger forward displacement than do targets that rotate upward (Munger & Minchew, 2002;Munger & Owens, 2004).…”
Section: Characteristics Of the Targetmentioning
confidence: 99%
“…Munger, Solberg, Horrocks, and Preston (1999) presented cube-shaped stimuli that rotated around different axes, and they reported that forward displacement was exhibited in all cases; however, if the axis of rotation was centered within the cube, there were no effects of direction of rotation on displacement, whereas if the axis of rotation was different from an axis of the cube, effects of direction of rotation were exhibited. presented shaded figures of three-dimensional objects, and they reported that implied rotation around an axis that corresponded with both the viewer's and the object's coordinate systems led to larger displacement than did rotation around an axis that corresponded with neither the viewer's nor the object's coordinate systems.…”
Section: Characteristics Of the Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the implied acceleration (Finke, Freyd, & Shyi, 1986), velocity (Freyd & Finke, 1985;Hubbard & Bharucha, 1988), and direction of motion (Halpern & Kelly, 1993;Hubbard, 1990;Munger, Solberg, Horrocks, & Preston, 1999) of a target modulate representational momentum for that target. The implied weight of a target (Hubbard, 1997) and the implied friction experienced by a target (Hubbard, 1995a(Hubbard, , 1998b) also modulate the effect.…”
mentioning
confidence: 99%